Analisis Keamanan Data dan Privasi dalam Penggunaan Metaverse di Indonesia - Gunawan Gunawan; Tata Sutabri (JOURNAL SAINS STUDENT RESEARCH, 2025)
Metaverse is currently a hot topic, especially with the advancement of existing digital technology. This is a desired world where someone can do various activities with their friends or often referred to as avatars. Although with many advantages, there are also issues of data security and user privacy.This study discusses the problem of using Metaverse in Indonesia. Guessing with qualitative methods and citing existing regulations, this study also reveals that many are not yet aware of the importance of protecting personal data and existing supervision is still minimal.Cooperation is needed between the government, developers and the community so that data protection is increasingly stable in the increasingly sophisticated digital era